Academic Senate Minutes 2010-09-02 - Academic Senate:::::::::
Chair Report. Correspondence received. Agenda amended and approved. Minutes of 4/29 and 5/13 approved. Faculty Eligible for Emeritus Status approved. Crash Course in Robert's Rules presentation. Diversity Mapping Event – co-sponsorship approved. President Report. Provost Report. Resolution in Support of the Director of Diversity and Inclusive Excellence and Resolution in Support of the Director of Undergraduate Studies – First Readings. Representative to the Associated Students Senate requested. Vice President of Administration and Finance Report. Vice President of SAEM Report. Associated Students Report. Statewide Senator Report. APC Report. EPC Report. FSAC Report. SAC Report. CFA Report. Group Photo.